2019
DOI: 10.2337/dc19-0571
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Liver Among Adolescent Offspring of Women With Type 1 Diabetes (the EPICOM Study)

Abstract: Intrauterine exposure to maternal type 1 diabetes is associated with a less favorable metabolic profile later in life. Nonalcoholic fatty liver disease is the hepatic manifestation of a cluster of metabolic abnormalities linked to insulin resistance. This study aimed to evaluate the effect of maternal pregestational type 1 diabetes on the presence of fatty liver in offspring and the association between maternal BMI, glycemic control during pregnancy, offspring metabolic risk factors, and offspring level of sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 40 publications
(40 reference statements)
0
23
1
Order By: Relevance
“…There was no association between maternal HbA1c during pregnancy and offspring FLI group. In OT1D, a WHtR>0.496 was associated with a significantly higher maternal HbA1c in the third trimester of pregnancy (p=0.04), but not in the pregestational period, the first or second trimester [25].…”
Section: Fatty Liver Diseasementioning
confidence: 91%
See 4 more Smart Citations
“…There was no association between maternal HbA1c during pregnancy and offspring FLI group. In OT1D, a WHtR>0.496 was associated with a significantly higher maternal HbA1c in the third trimester of pregnancy (p=0.04), but not in the pregestational period, the first or second trimester [25].…”
Section: Fatty Liver Diseasementioning
confidence: 91%
“…In contrast, Weiss et al showed that metabolic differences were more distinct in male than in female offspring [24]. In Knorr et al, there was a higher female proportion in the groups with FLI 30-60 and FLI60, although the difference between FLI groups was not significant [25]. In addition, the group with WHtR>0.469 included significantly more females (p=0.01) [25].…”
Section: Sex Differencesmentioning
confidence: 93%
See 3 more Smart Citations